Banco de dados orais: uma nova perspectiva aos estudos do português brasileiro (Revista de Estudos da Linguagem, 2004)
This work represents an attempt to facilitate the automatic accessto the spontaneous Portuguese data for studies on experimentalphonetic area and speech synthesis, maintaining qualitative andquantitative information of the data. This corpus constitutes morethan 30 hours of recording with samples of two Portuguese spokendialects in Amazonia Region: the Amazon Portuguese (AM) and theAfro-Brazilian Portuguese (ABP). As a baseline, samples of the StandardBrazilian Portuguese (PB) were also used. The corpus inventory,the digitalization of the speech data and the phonetic segmentationusing the PRAAT software preceded the construction of the oral database.Using language HTML and other resources of computer science adocumentation of the database in a Internet site becomes possible.